Glycan Diversity in Fungi, Bacteria and Sea Organisms - Eliana Barreto-Bergter (Frontiers Research Topics, 2016)
The cell surface of fungi, bacteria and sea organisms is highly glycosylated. These glycans are oligo- or polysaccharide molecules that can be secreted or attached to protein or lipids forming glycoconjugates. They present extraordinary structural diversity that could explain their involvement in many fundamental cellular processes, including growth, differentiation and morphogenesis. Considerable advances have been made on the structural elucidation of these glycans. Their primary structures were determined based on a combination of mass spectrometry and NMR spectroscopy techniques. The combination of these sensitive and powerful techniques has allowed us to increase our structural knowledge of a wide variety of glycans expressed by different fungi, bacteria and sea organisms.